THE INFLUENCE OF STORE LAYOUT, INTERIOR DISPLAY, AND HUMAN VARIABLE RELATED TO SHOPPING ORIENTATION AT MATAHARI BASKO GRAND MALL PADANG - Ainil Mardiah (Universitas Negeri Padang, 2019)
This research was determine the effects of store layout, interior display, and human variable related to shopping orientation at Matahari Basko Grand Mall Padang. This research have done by customer Matahari Basko Grand Mall Padang. The population of this research were all of the customer Matahari Basko Grand Mall Padang in Padang City, and the sample was 100 respondent. The technic sampling in this research was propability sampling with the accidental sampling. The technic of analysis data used Multiple Regression by SPSS Version. 16.0 program. This results showed that store layout have positive and significant effect related to shopping orientation, with the calculation gained (tcount = 2,568 dan Sig. 0,012 < 0,05), interior display have positive and significant effect related to shopping orientation, with the calculation gained (tcount = = 2,568 and Sig. 0,012 < 0,05), and human variables have positive and not significant effect related to shopping orientation at Matahari Basko Grand Mall Padang.Keywords : Shopping Orientation, , Store Layout, Interior Display, dan Human.